Complex assessment of conductive heart system and myocardial electric instability in arterial hypertension patients - B. G. Iskenderov; T. V. Lokhina; V. A. Lyusov; V. Yu. Kapelovich (Российский кардиологический журнал)
The study included 86 patients aged 42;57 years, with Stage II essential arterial hypertension (AH) and no antihyperten; sive therapy during the study. All participants underwent 24;hour blood pressure (BP) monitoring, diagnostic transesophageal left atrium electrostimulation, and echocardiography. QT interval length and dispersion, as well as RR interval variability (SDNN) were analyzed. In AH patients, left ventricular hypertrophy (LVH), metabolic syndrome and pathologic types of cir; cadian BP profile were associated with sino;atrial node function suppression, and increased atrial and ventricular electric instability. Adverse electrophysiologic prognostic parameters, cardiac rhythm disturbance predictors, were diagnosed in high; risk group by 3;5 times more often than in patients without LVH or MS and with normal circadian BP profile. Therefore, car; diac electric remodeling, associated with LVH, MS, and circadian BP rhythm disturbances, increased electric instability and arrhythmia risk.